The sea, identity and history : from the Bay of Bengal to the South China sea - International Seminar on Maritime Cultures and Traditions of the Bay of Bengal : (2011 : New Delhi); Chandra, Satish; Ray, Himanshu Prabha; Society for Indian Ocean Studies (Singapore : ISEAS Publishing, Institute of Southeast Asian Studies, 2013)
Contributed research papers presented in seminar organized by the Society for Indian Ocean Studies at Mehru Memorial Museum and Library, New Delhi on 22-23 April, 2011.
Includes bibliographical references and index.
Keywords: Geopolitics -- Indian Ocean Region; Indian Ocean -- Strategic aspects; Indian Ocean region -- Politics and government; Indian Ocean Region -- History -- Congresses -- Commerce; Indian Ocean Region -- Foreign relations -- Congresses